Rehabilitation and nutrition protocols for optimising return to play from traditional ACL reconstruction in elite rugby union players: A case study - Shaw, G.; Serpell, B.; Baar, K. (Journal of Sports Sciences, 2019)
Current nutrition and exercise focus during rehabilitation periods has been on reducing muscle atrophy associated with immobilisation. This case report outlines a best practice anterior cruciate ligament (ACL) rehabilitation programme undertaken by two professional rugby athletes, with the addition of an evidence-based supplementation (gelatine and vitamin C) and exercise protocol focused on collagenous tissue. Both players ruptured their left ACL and were repaired with a traditional hamstring graft. Players undertook a structured rehabilitation programme for 34 weeks before being clinically assessed ready to play. Players saw minimal changes in body composition in the early rehabilitation period (P1 - 0.8 kg; P2 - 0.4 kg). Leg lean mass reduced in both legs of Player 1 (Injured - 0.8 kg, Non-injured - 0.6 kg) at 17 weeks, with Player 2 only experiencing a loss of 0.3 kg of lean tissue in the injured leg. Both players returned to baseline body compositions after 24 weeks. Leg strength returned to a maximum at 24 and 15 weeks, respectively, with knee function returning to baseline by 30 weeks. This case report provides evidence that nutrition and rehabilitation programmes targeted at minimising the effects of disuse in both muscle and connective tissue may assist return to play after ACL injury.